1997
DOI: 10.1111/j.1751-1097.1997.tb08644.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Both Type I and Type II Mechanisms in M13 Virus Inactivation by Methylene Blue Photosensitization

Abstract: We have investigated the mechanism of virus photoinactivation with methylene blue (MB) by conducting deuterium oxide (D2O), azide ion (N3-) and oxygen-dependent studies. Inactivation of M13 bacteriophage and singlet oxygen (1O2) generation by MB photosensitization were irradiation dose dependent. Inactivation of M13 was enhanced by D2O and inhibited by N3-, suggesting that 1O2 participates in M13 inactivation by MB photosensitization. However, N3- did not inhibit M13 inactivation completely. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The wavelength-dependent complex RIs of representative materials at two different wavelengths (514 and 633 nm) are summarized in Table 1 [23], polystyrene [24], cellulose [25], oxy-hemoglobin (HbO 2 ) [26], 5CB liquid crystal [27], ethanol [28], acetic acid [29], methanol [29], human tissue (dermis) [30], and water [31]; (b) eumelanin [32], deoxy-and oxy-hemoglobin (Hb and HbO 2 ) [33], mammalian fat [34], riboflavin [35], nile red in dioxane [36], methylene blue [37], boron subphthalocyanine chloride in benzene [38], and water [39]. two wavelengths are chosen because they are available from the most widely accessible lasers (Ar ion and He-Ne laser) in the visible range and also can provide reasonable optical dispersion for biomolecules.…”
Section: A Wavelength-dependent Ri and Molecular Informationmentioning
confidence: 99%
“…The wavelength-dependent complex RIs of representative materials at two different wavelengths (514 and 633 nm) are summarized in Table 1 [23], polystyrene [24], cellulose [25], oxy-hemoglobin (HbO 2 ) [26], 5CB liquid crystal [27], ethanol [28], acetic acid [29], methanol [29], human tissue (dermis) [30], and water [31]; (b) eumelanin [32], deoxy-and oxy-hemoglobin (Hb and HbO 2 ) [33], mammalian fat [34], riboflavin [35], nile red in dioxane [36], methylene blue [37], boron subphthalocyanine chloride in benzene [38], and water [39]. two wavelengths are chosen because they are available from the most widely accessible lasers (Ar ion and He-Ne laser) in the visible range and also can provide reasonable optical dispersion for biomolecules.…”
Section: A Wavelength-dependent Ri and Molecular Informationmentioning
confidence: 99%
“…However, photoinactivation occurred even in the presence of sodium azide, suggesting that both type I and type II mechanisms may be involved in the M13 photoinactivation process. In the presence of quencher concentrations ranging from 3.5 to 35 mM, a sodium azide protective effect was not observed, as evidenced by increasing rates of M13 phage photoinactivation, reaching a plateau thereafter [52]. Also, the effect of singlet oxygen quenchers and of hydrogen peroxide indicated singlet oxygen as the main factor responsible for the loss of biological activity of bacteriophage M13 by rose bengal [51].…”
Section: Mechanisms Of Photodynamic Inactivationmentioning
confidence: 99%
“…The results also showed that the efficacy of T4-like phage inactivation, using the same fluence rate, was dependent on the light source used, in particular when the light is delivered at a low fluence rate. M13 phage was phototreated with 5.0 μM MB and was inactivated in an irradiation dose-dependent manner [52]. Kastury and Platz [58] showed that increasing the concentration of a PS at a fixed light dose leads to increased viral inactivation as does an increase in the total light exposure at a fixed PS concentration.…”
Section: Factors Affecting Viral Pdimentioning
confidence: 99%
See 1 more Smart Citation
“…For oxygen‐dependence experiments, an Ar bubbling method was used as previously described (19). In brief, 2 mL of M13 suspension in a screw‐cap cuvette sealed with a silicon septum was placed in a fluorospectrometer.…”
Section: Methodsmentioning
confidence: 99%